1976
DOI: 10.1111/j.1469-8137.1976.tb01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion Uptake in Relation to the Development of a Root Hypodermis

Abstract: SUMMARY The suberization of the outer cortical cells in the basal zones of maize roots to form a hypodermis reduced the radial movement of phosphate towards the stele. Suberization of these cells appeared to place a far greater restriction on the translocation of phosphate to the shoot than the suberization of the endodermis. Under the same conditions as were used for growing maize, barley roots did not develop a hypodermis, and phosphate movement from the basal zones of the root axes was not restricted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 7 publications
2
17
0
2
Order By: Relevance
“…This ion did, therefore, pass through an intact, mature exo-and endodermis. The less efficient radial transport in the old zone (compared to that of the young zone) could be a consequence of the presence of suberin lamellae in both the endo-and exodermis, as similar results were previously obtained with marrow and barley (Harrison-Murray and Clarkson, 1973;Robards et al, 1973;Ferguson and Clarkson, 1976).…”
Section: Sites Of Ca 21 Uptake and Axial Transport Along Onion Rootssupporting
confidence: 74%
“…This ion did, therefore, pass through an intact, mature exo-and endodermis. The less efficient radial transport in the old zone (compared to that of the young zone) could be a consequence of the presence of suberin lamellae in both the endo-and exodermis, as similar results were previously obtained with marrow and barley (Harrison-Murray and Clarkson, 1973;Robards et al, 1973;Ferguson and Clarkson, 1976).…”
Section: Sites Of Ca 21 Uptake and Axial Transport Along Onion Rootssupporting
confidence: 74%
“…In the older roots of most monocots and some dicots, the presence of a hypodermis has been demonstrated (8,9,22). In detailed work involving fluorescence microscopy of cell walls and studies on the movement of apoplastic dyes in corn and onion roots, Peterson and coworkers have demonstrated that the hypodermis appears to be an apoplastic barrier to the diffusion of high mol wt dyes which bind to cell walls (22)(23)(24).…”
mentioning
confidence: 99%
“…Lamelas de suberina na endoderme têm sido registradas por diversos autores (Enstone et aI. 2002, Arias & Sánchez 2004, Rodrigues & Estelita 2004, estando envolvida com restrição da translocação radial de íons do córtex para o esteIo (Ferguson & Clarkson 1976). Cabe ressaltar que as estrias são visíveis, em microscopia óptica, somente quando as paredes ainda não apresentam espessamento.…”
Section: Resultsunclassified